Synthesis of aminopyrazole analogs and their evaluation as CDK inhibitors for cancer therapy. Issue 23 (15th December 2018) - Rana, Sandeep; Sonawane, Yogesh A.; Taylor, Margaret A.; Kizhake, Smitha; Zahid, Muhammad; Natarajan, Amarnath
Graphical abstract: Highlights: A series of aminopyrazole based CDK2/5 were designed and synthesized. A screening funnel of cell-free and caspase 3/7 assay identified three analogs. Growth inhibition studies in a panel of pancreatic cancer cell lines revealed analog 24 as a lead compound. In vitro selectivity assay against a panel of kinases showed excellent selectivity for CDK2 and CDK5. Abstract: We synthesized a library of aminopyrazole analogs to systematically explore the hydrophobic pocket adjacent to the hinge region and the solvent exposed region of cyclin dependent kinases. Structure-activity relationship studies identified an optimal substitution for the hydrophobic pocket and analog24 as a potent and selective CDK2/5 inhibitor.